Extremism, racism and riots: exploring the political, social and cultural determinants of poor mental health - Kamaldeep Bhui; Dianndra Roberts; Myrna Lashley; Edgar Jones; Kenneth R. Kaufman (BJPsych Open)
The UK has seen an outbreak of riots after the death of three children in a knife attack. Misinformation about the suspect's heritage and religion was spread by social media, which was then used to incite violence and racism resulting in damage to property, terror and injuries. We put forward arguments that this was an extremist act and draw on the literature on terrorism, extremism and identity to put forward a deeper analysis of how this happened and what can be done to prevent future riots. We bring an interdisciplinary perspective drawing on research from social, cultural, psychological and political perspectives.